THE USE OF DISCOVERY METHOD IN TEACHING READING COMPREHENSION ON NARRATIVE TEXT - Kurniadi, Putra; Regina, Regina; Rezeki, Yanti Sri (Journal of English Education Program, 2020)
The purpose of this research is to investigate the effectiveness of discovery method in teaching reading comprehension. The design of research used is a pre-experimental research, and the data were collected by using measurement technique with multiple-choice reading test as the tool of collecting data. The obtained data were analyzed by using t-test. The results of data analysis showed that discovery method has the effect on the students’ ability in reading comprehension. The mean score of the students’ pre-test was 58.2 whereas the mean score of post-test was 64.8. The effect size of the treatment was 0.98 which is categorized as moderate effect. Thus, the alternative hypothesis that the use of discovery method in teaching reading comprehension on narrative text is effective to the eighth-grade students of SMP Kartika Kubu Raya in academic year 2016/2017. Therefore, the researcher believes the teachers can use the discovery method in their teaching learning process, especially in reading comprehension on narrative text.